Detection and consequences of atmospheric deserts: insights from a case study - F. Fix; G. Mayr; A. Zeileis; I. Stucke; R. Stauffer (Weather and Climate Dynamics)
We introduce the concept of atmospheric deserts (ADs), air masses that are advected away from hot and dry convective boundary layers in semi-arid or desert source regions. They can be expected to eliminate cloudiness, cause heat to build up in the target region, suppress thunderstorm formation in their centre, and boost thunderstorm formation at their edges. A direct detection method tracing the AD from source to target using Lagrangian trajectories is developed.